THE Grammar Lesson by Grammarians and Rhetoricians - Hashim Mohammed, Amer (Journal of College of Education, 2022)
The study aims at explaining the definition of the grammar science in the literature of the linguistics and the differences between grammar and rhetoric science in characteristics and the subjects. Old studies are still the main source for the new studies with the same in all language concepts moreover new studies can’t be constructed without depending on the approaches of old studies or the ones that close to the old ones. This study present the differences between grammar and rhetoric science with historical background literature for each of them, and showing the literary criticism that lead to explanation and adoption for the concepts of grammar science and fields of study and this study shows what makes grammar science unique in all linguistics sciences.
Keywords: The Lesson; Grammar; Rhetoric